Mortality levels and trends by HIV serostatus in rural South Africa: Nyirenda, Makandwe; Hosegood, Victoria; Bärnighausen, Till; Newell, Marie-Louise - Nyirenda, Makandwe; Hosegood, Victoria; Bärnighausen, Till; Newell, Marie-Louise (AIDS <London>, 2007)
Objective: To examine mortality differentials in HIV-infected and uninfected adults by demographic characteristics and the effect of non-testing on the level and pattern of age-sex specific mortality. Methods: Three annual prospective population-based HIV surveys between 2003 and 2006 provide information about births, deaths, migrations and other demographic, health and socioeconomic data. Deaths and person-years of exposure were aggregated for each calendar year between 2004 and 2006, from which mortality rates were derived. The association between risk factors and mortality was assessed using a Cox proportional hazards model.
Gesehen am 23.06.2017